2019
DOI: 10.3201/eid2505.181076
|View full text |Cite
|
Sign up to set email alerts
|

Nipah Virus Sequences from Humans and Bats during Nipah Outbreak, Kerala, India, 2018

Abstract: We retrieved Nipah virus (NiV) sequences from 4 human and 3 fruit bat ( Pteropus medius ) samples from a 2018 outbreak in Kerala, India. Phylogenetic analysis demonstrated that NiV from humans was 96.15% similar to a Bangladesh strain but 99.7%–100% similar to virus from Pteropus spp. bats, indicating bats were the source of the outbreak.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
66
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(72 citation statements)
references
References 13 publications
(14 reference statements)
1
66
0
Order By: Relevance
“…In the current study, observed seroprevalence patterns and the fitted model suggest that three periods of transmission occurred over the 6 y of sampling, each of which followed periods of low adult and juvenile seroprevalence. Viral detection in bats has coincided with some human outbreaks, supporting the hypothesis that spillover is a sporadic event (67,97). In our study periods, low seroprevalence in bats was not always followed by outbreaks in humans.…”
Section: Discussionsupporting
confidence: 85%
“…In the current study, observed seroprevalence patterns and the fitted model suggest that three periods of transmission occurred over the 6 y of sampling, each of which followed periods of low adult and juvenile seroprevalence. Viral detection in bats has coincided with some human outbreaks, supporting the hypothesis that spillover is a sporadic event (67,97). In our study periods, low seroprevalence in bats was not always followed by outbreaks in humans.…”
Section: Discussionsupporting
confidence: 85%
“…During the Kerala outbreak, fever, myalgia, respiratory difficulties, headache, vomiting, cough, altered sensorium and encephalitis with seizures were reported in infected persons. Outbreaks in Bangladesh and India showed a higher number of cases with respiratory distresses [48].…”
Section: Clinical Featuresmentioning
confidence: 98%
“…3 from Bangladesh (AY988601.1, JN808857.1, AY988601.1) [48] and 5 from India (MH523641.1, MH523642.1, MH396625.1, MH523640.1, FJ513078.1) [49] were retrieved from their translated genomes deposited in the NCBI nucleotide database [50] and were used to identify sequence variations in proteins. We also verified that the translated protein sequences of the Malaysian strain matched with those of the protein sequences deposited in SwissProt [51].…”
Section: Mapping Strain Variants Onto Structurementioning
confidence: 99%
“…At the time of modelling the NiV proteins, the sequence data from the 2018 outbreak was not available [49]. Hence, all the modelling was done by considering that sequence of the Malaysian strain.…”
Section: Sequence Variations In Niv Isolatesmentioning
confidence: 99%